1991
DOI: 10.1084/jem.173.4.793
|View full text |Cite
|
Sign up to set email alerts
|

Immunity to a pulmonary Cryptococcus neoformans infection requires both CD4+ and CD8+ T cells.

Abstract: SummaryThe role of CD4+ and CD8+ T cells in mediating pulmonary clearance of a cryptococcal infection was investigated . Intratracheal inoculation ofBALB/c and C.B-17 mice with a moderately virulent strain of Cryptococcus neoformans (52D) resulted in a pulmonary infection, which was cleared by a T cell-dependent mechanism . During this clearance, there was a significant influx of both CD4+ and CD8+ T cells into the lungs . Depletion of CD4+ T cells by injections of CD4-specific monoclonal antibody (mAb) preven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
172
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(181 citation statements)
references
References 47 publications
7
172
1
1
Order By: Relevance
“…Classically, defects in cellular immunity, particularly those that require T lymphocytes, are considered as the main risk factor for the mycosis, both in humans and mice (3,4). In the present study, it was observed that the susceptible mouse strain produced the highest amount of crossreactive antibodies.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Classically, defects in cellular immunity, particularly those that require T lymphocytes, are considered as the main risk factor for the mycosis, both in humans and mice (3,4). In the present study, it was observed that the susceptible mouse strain produced the highest amount of crossreactive antibodies.…”
Section: Discussionsupporting
confidence: 51%
“…C. neoformans has a polysaccharide capsule composed of glucuronoxylomannan (GXM), which acts as a major virulence factor (2) and is considered to be a thymus independent type-2 antigen (TI-2). A murine model in which C. neoformans is inoculated via intratracheal route has allowed the definition of different levels of susceptibility among the various mouse strains (3,4). It has been proposed that these differences are attributed mainly to the presence of a Th1 cellular immune response (3).…”
mentioning
confidence: 99%
“…33 Th cells are central regulators of anticryptococcal immune responses. 25,34,35 Although Th2 responses are detrimental, 11,15 Th1 and Th17 responses are protective. 7,9,25,35,36 To gain a deeper insight into the Th cytokine profile in the absence of eosinophils, we analyzed IL-4, IFN-␥, and IL-17A production by pulmonary Th cells on infection of WT and eosinophil-deficient ⌬dblGATA mice.…”
Section: In the Absence Of Eosinophils Th2 Responses Are Reduced Andmentioning
confidence: 99%
“…In immune deficient patients, dissemination of the pathogen occurs due to the inability of the host to limit the infection (21,22). Protection from C. neoformans infection depends on both CD4 ϩ and CD8 ϩ T cells (23)(24)(25)(26). Although both lymphocyte subsets may affect the pathogen directly, indirect immune activation of NK cells (27), neutrophils, and macrophages (28) may also confer host resistance.…”
Section: O Ptimal Activation Of Naive T Cells Requires Two Signalsmentioning
confidence: 99%